Hermeneutical Reading of á¹¬alÄq - Rusli, Rusli (Hunafa: Jurnal Studia Islamika, 2015)
This paper deals with the hermeneutical reading of divorce (á¹¬alÄq), one of the sensitive issues in Islamic family law. It is concluded that the existence of Islamic law of divorce is not to denigrate women; however, it is to give respons to the injustice suffered by women by giving regulations that are more friendly to women. The regulations of the Quran on the subject of divorce are designed to restrict the practice which had prevailed among the Arabs that they are free to divorce his wife at any time without any reason, and remarry her in unlimited ways. This is indicated that Islam stipulates that divorce is two times: then one may retain with goodness (and reasonable terms), or let go with goodness and reasonable terms. If divorce occurs, a divorced woman should the prescribed period (âiddah) and financial consideration (mutâat al-á¹¬alÄq).